Return to sports in the COVID-19 era: a clinical review - Harvey, B.; Stork, N. (The Journal of Urgent Care Medicine, 2021)
The COVID-19 worldwide pandemic has changed sports as we know it. Returning athletes back to sport safely continues to be widely debated among physicians in cardiology, primary care, infectious disease, and sports medicine. The return-to-play process after a COVID-19 infection will depend on the severity of their infection, duration of symptoms in the context of any concerning past medical history, and/or family history. Urgent care providers should be prepared to conduct "clearance" exams and provide guidance on safe return to the playing field.